PERAN GURU DALAM PEMBELAJARAN DARING DI SEKOLAH DASAR PADA MASA PANDEMI - Nurohimah Puji Astuti; Probosiwi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article explains the teacher's role as a teacher, facilitator, motivator, and evaluator and the supporting and inhibiting factors of the teacher’s role in online learning of Javanese language subjects. The study used a qualitative research type with a descriptive approach. The subjects of the study involved the principal, Javanese language teacher, and third-grade students of SD Muhammadiyah Karangturi. Data collection techniques were carried out through interviews, observation, and documentation. The validity of the data used triangulation of sources, methods, and data. Data analysis used the Miles and Huberman model, namely data collection, data reduction, data presentation, and conclusions. The result indicated that the teacher’s role as a teacher, facilitator, motivator, and evaluator in online learning in Javanese language subjects has been implemented well. It is evidenced by the teacher consistently applying and adapting to online technology in order to make students learnt optimally. Subsequently, the supporting factors for implementing the teacher’s role were supported by the book, technology facilities, and internet quota supported by the government. Inhibiting factors occurred due to lack of motivation to learn and busy parents in working.